INFLUENCE OF OUTDOOR LEARNING APPROACHES TO STUDENT'S BIOLOGY LEARNING RESULT - Destriani, Destriani; Nopriyeni, Nopriyeni; Irwandi, Irwandi; Irdalisa, Irdalisa (Dharmas Education Journal (DE_Journal), 2023)
This study aims to determine the effect of the outdoor learning approach on students' biology learning outcomes. This research was conducted in February - March 2023. The research location was carried out to class VII students of SMPN 14 Bengkulu City by giving test questions. This type of research is quantitative research using a quasi-experimental research design. The implementation used 2 research groups, namely the experimental class group and the control class group. The population in this study were all students of class VII SMPN 14 Bengkulu City as many as 231 people consisting of 8 classes for random sampling obtained class 7.2 which totaled 32 consisting of 18 boys. 14 girls and class 7.1 which totaled 32 consisting of 16 boys 16 girls. The data collection method was in the form of tests taken directly from the pretest and posttest scores of student learning outcomes in both the experimental class and the control class. The results of the study show that: There is an effect of Outdoor Learning on biology learning outcomes for class VII students. This can be seen from the results of the average pretest score of the experimental class and the average pretest score of the control class, the average posttest score of the experimental class is greater than the average posttest score of the experimental class. control class. So it can be concluded that H0 is rejected and H1 is accepted, meaning that there is an influence of the outdoor learning approach on the learning outcomes of class VII students. So it can be concluded that H0 is rejected and H1 is accepted, meaning that there is an influence of the outdoor learning approach on the learning outcomes of class VII students of SMPN 14 Bengkulu City.